Antifibrotic Mechanism of Cinobufagin in Bleomycin-Induced Pulmonary Fibrosis in Mice - Li, Xiaohe; Bi, Zhun; Liu, Shuaishuai; Gao, Shaoyan; Cui, Yunyao; Huang, Kai; Huang, Mengying; Mao, Jiahe; Li, Lixin; Gao, Jingjing; Sun, Tao; Zhou, Honggang; et al. (Frontiers in Pharmacology, 2019)
Idiopathic pulmonary fibrosis (IPF) is a progressive and usually fatal lung disease that is characterized by fibroblast proliferation and extracellular matrix remodeling, which result in irreversible distortion of the lung’s architecture and the formation of focal fibrous hyperplasia. The molecular mechanism by which pulmonary fibrosis develops is not fully understood, and no satisfactory treatment currently exists. However, many studies consider that aberrant activation of TGF-β1 frequently promotes epithelial-mesenchymal transition (EMT) and fibroblast activation in pulmonary fibrosis. Cinobufagin (CBG), a traditional Chinese medicine, has been widely used for long-term pain relief, cardiac stimulation, and anti-inflammatory and local anesthetic treatments. However, its role in pulmonary fibrosis has not yet been established. We investigated the hypothesis that cinobufagin plays an inhibitory role on TGF-β1 signaling using a luciferase-reporter assay. We further explored the effect of cinobufagin on pulmonary fibrosis both in vitro and in vivo. The in vitro experiments showed that cinobufagin suppresses TGF-β1/Smad3 signaling in a dose-dependent manner, attenuates the activation and differentiation of lung fibroblasts and inhibits EMT induced by TGF-β1 in alveolar epithelial cells. The in vivo experiments indicated that cinobufagin significantly alleviates bleomycin-induced collagen deposition and improves pulmonary function. Further study showed that cinobufagin could attenuate bleomycin-induced inflammation and inhibit fibroblast activation and the EMT process in vivo. In summary, cinobufagin attenuates bleomycin-induced pulmonary fibrosis in mice via suppressing inflammation, fibroblast activation and epithelial-mesenchymal transition.